Associations between adolescent media use, mental health, and risky sexual behaviors. (August 2019) - Merrill, Renae A.; Liang, Xinya
Abstract: Guided by the ecological "technosystem, " data was examined from 13, 156 adolescents completing the CDC's 2015 Youth Risk Behavior Surveillance System (YRBSS) looking for associations between television, social media, depressive symptoms, suicidality, and sexual risk behaviors. Regression results indicate media use is not an important factor in adolescents' internalizing and externalizing problems. Social media and television are unlikely the contributors to both mental health and risky sexual behaviors. Findings from this research are important for future studies that focus on multi-systemic prevention and intervention efforts aimed at promoting adolescent resiliency, particularly among vulnerable youth who are most susceptible to media influences. Highlights: Social media consumption and TV may not be practically associated with poorer mental health. Both social media and hours spent watching TV had negligible impacts on risky sexual behaviors. Adolescents who engaged in risky sexual behaviors reported overall poorer mental health.